Suspected Heparin-Induced Thrombocytopenia in Patients Receiving Extracorporeal Membrane Oxygenation - Natt, Bhupinder (J Extra Corpor Technol, 2017)
Heparin-induced thrombocytopenia (HIT) is an immune reaction usually secondary to unfractionated heparin. Anticoagulation management is critical in patients while on extracorporeal membrane oxygenation (ECMO) to prevent thromboembolism and for the optimal functioning of the circuit. We identified five patients with respiratory failure at our hospital managed with ECMO in the last 2 years that were treated for HIT. A brief clinical course and their management are discussed. We also briefly review the literature for best evidence for management of such patients.